Electrowetting-on-dielectric powered by triboelectric nanogenerator. (July 2022) - Wang, Chao; Li, Xiangming; Qiu, Yangfan; Wang, Liang; Li, Congming; Liu, Guifang; Liu, Gangqiang; Zheng, Qinwen; Chen, Xiaoliang; Tian, Hongmiao; Wang, Chunhui; Shao, Jinyou
Abstract: Electrowetting-on-dielectric (EWOD) is a versatile technique for controlling the liquid-wetting behavior of solid surfaces, but usually relies on bulky and complex power suppliers for high driving voltages, which largely limits the practical applications toward miniaturization, portability, and multifunctional integration. Here, a mechanical stimuli-controlled EWOD strategy powered by a triboelectric nanogenerator (TENG) with tunable high-voltage output is demonstrated, which allows for manipulating liquid wettability by mechanical stimuli. The physical behaviors of the voltage transfer and contact angle response during the TENG-driven EWOD process are experimentally investigated, and the underlying mechanisms are revealed by a circuit model, which can give general guidance for the design and optimization of the mechanical stimuli-controlled EWOD systems. As a derived application of this strategy to the microfabrication field, a self-powered electrocapillary infilling and micromolding method is further developed, which allows for fabricating the originally difficult-to-mold microstructures in a handy way. This mechanical stimuli-controlled TENG-driven EWOD strategy also shows general applicability for different liquid systems of not only the liquid prepolymer but also the DI water and ionic liquid, which can potentially extend to more functional applications involving tunable wettability or liquid infilling/permeation, such as wearable microfluidics or lab-on-chip, electrolyte infilling for porous electrodes, and on-demand drug permeation systems. Graphical Abstract: ga1 Highlights: A mechanical stimuli-controlled EWOD strategy powered by TENG is demonstrated for manipulating liquid wettability. The physical behaviors during the TENG-driven EWOD process are systematically investigated and the mechanisms are revealed. This strategy is applicable for different liquid systems, such as the liquid prepolymer, DI water and ionic liquid. A self-powered electrocapillary infilling and micromolding method is further developed for fabricating microstructures.